Big Five Personality and Creativity: The Moderating Effect of Motivational Goal Orientation. (18th September 2017) - Kaspi‐Baruch, Oshrit
Abstract: This study examined the association between the big five personality dimensions and creativity through the moderation of motivational goal orientation. One hundred and ninety students engaged in full‐time employment completed questionnaires, which were used to assess the variables of interest. Regression moderation analyses supported some of the expected hypotheses. The associations between the big five dimensions and creativity were moderated by learning motivational goal orientation. Individuals high in extroversion, emotional stability, and low in conscientiousness, are most creative when they are oriented toward learning. In addition, openness fully predicted creativity, without the moderation of goal orientation. The results are discussed in terms of the interactional nature of personality and goal orientation theory.